Sickle cell disease in Sicily. Issue 1 (February 1980) - Roth, E F; Schiliro, G; Russo, A; Musumeci, S; Rachmilewitz, E; Neske, V; Nagel, R
Abstract : The chemical and physical properties of haemoglobin S derived from homozygotes for this haemoglobin in Sicily were examined, as well as some erythrocytic characteristics. Sicilian Hb S was identical to that found in USA black patients in electrophoretic mobility on both starch and citrate agar media, solubility, mechanical precipitation rate of oxyhaemoglobins, and minimum gelling concentration, as well as by peptide mapping and amino-acid analysis of all beta-chain peptides. Taken together with the presence in Sicily of African blood group markers and certain historical considerations, it seems clear that the source of Hb S in Sicily is Africa. While the clinical severity in nine Sicilian children did not seem remarkably different from the disease in the USA, the most severe and fatal complications were not seen. Mean Hb F Was 10.5% and 2, 3-diphosphoglycerate (2, 3-DPG) values were higher in Sicilian homozygotes than in black USA counterparts (21.79 mumol/g Hb vs 15.16). Red cell AT values were also slightly higher in Sicilian patients. The presence of concomitant thalassaemia was excluded by both family studies and globin chain synthetic ratios. In conclusion, haemoglobin S in Sicilian homozygotes is identical to Hb S found in USA blacks. Although the severity of the disease seems quite similar in both groups of patients, other erythrocytic properties were found to be different. Whether these factors influence severity remains to be elucidated.